2023-05-08 19:18:12 +00:00
|
|
|
|
import Mathlib.Data.Real.Basic
|
|
|
|
|
|
2023-05-08 19:37:02 +00:00
|
|
|
|
import Common.Real.Int
|
|
|
|
|
|
2023-05-08 19:18:12 +00:00
|
|
|
|
/-! # Exercises.Apostol.Exercises_1_11 -/
|
|
|
|
|
|
|
|
|
|
namespace Exercises.Apostol.Exercises_1_11
|
|
|
|
|
|
|
|
|
|
/-! ## Exercise 4
|
|
|
|
|
|
|
|
|
|
Prove that the greatest-integer function has the properties indicated.
|
|
|
|
|
-/
|
|
|
|
|
|
|
|
|
|
/-- ### Exercise 4a
|
|
|
|
|
|
|
|
|
|
`⌊x + n⌋ = ⌊x⌋ + n` for every integer `n`.
|
|
|
|
|
-/
|
|
|
|
|
theorem exercise_4a (x : ℝ) (n : ℤ) : ⌊x + n⌋ = ⌊x⌋ + n := by
|
|
|
|
|
sorry
|
|
|
|
|
|
|
|
|
|
/-- ### Exercise 4b
|
|
|
|
|
|
|
|
|
|
`⌊-x⌋ = -⌊x⌋` if `x` is an integer.
|
|
|
|
|
`⌊-x⌋ = -⌊x⌋ - 1` otherwise.
|
|
|
|
|
-/
|
|
|
|
|
theorem exercise_4b (x : ℝ)
|
|
|
|
|
: (Real.isInt x → ⌊-x⌋ = -⌊x⌋)
|
|
|
|
|
∨ (¬Real.isInt x → ⌊-x⌋ = -⌊x⌋ - 1) := by
|
|
|
|
|
sorry
|
|
|
|
|
|
|
|
|
|
/-- ### Exercise 4c
|
|
|
|
|
|
|
|
|
|
`⌊x + y⌋ = ⌊x⌋ + ⌊y⌋` or `⌊x⌋ + ⌊y⌋ + 1`.
|
|
|
|
|
-/
|
|
|
|
|
theorem exercise_4c (x y : ℝ)
|
|
|
|
|
: ⌊x + y⌋ = ⌊x⌋ + ⌊y⌋ ∨ ⌊x + y⌋ = ⌊x⌋ + ⌊y⌋ + 1 := by
|
|
|
|
|
sorry
|
|
|
|
|
|
|
|
|
|
/-- ### Exercise 4d
|
|
|
|
|
|
|
|
|
|
`⌊2x⌋ = ⌊x⌋ + ⌊x + 1/2⌋`
|
|
|
|
|
-/
|
|
|
|
|
theorem exercise_4d (x : ℝ)
|
|
|
|
|
: ⌊2 * x⌋ = ⌊x⌋ + ⌊x + 1/2⌋ := by
|
|
|
|
|
sorry
|
|
|
|
|
|
|
|
|
|
/-- ### Exercise 4e
|
|
|
|
|
|
|
|
|
|
`⌊3x⌋ = ⌊x⌋ + ⌊x + 1/3⌋ + ⌊x + 2/3⌋`
|
|
|
|
|
-/
|
|
|
|
|
theorem exercise_4e (x : ℝ)
|
|
|
|
|
: ⌊3 * x⌋ = ⌊x⌋ + ⌊x + 1/3⌋ + ⌊x + 2/3⌋ := by
|
|
|
|
|
sorry
|
|
|
|
|
|
|
|
|
|
/-- ### Exercise 5
|
|
|
|
|
|
|
|
|
|
The formulas in Exercises 4(d) and 4(e) suggest a generalization for `⌊nx⌋`.
|
|
|
|
|
State and prove such a generalization.
|
|
|
|
|
-/
|
|
|
|
|
theorem exercise_5 (n : ℕ) (x : ℝ)
|
|
|
|
|
: ⌊n * x⌋ = 10 := by
|
|
|
|
|
sorry
|
|
|
|
|
|
|
|
|
|
/-- ### Exercise 7b
|
|
|
|
|
|
|
|
|
|
If `a` and `b` are positive integers with no common factor, we have the formula
|
|
|
|
|
`Σ_{n=1}^{b-1} ⌊na / b⌋ = ((a - 1)(b - 1)) / 2`. When `b = 1`, the sum on the
|
|
|
|
|
left is understood to be `0`.
|
|
|
|
|
|
|
|
|
|
Derive the result analytically as follows: By changing the index of summation,
|
|
|
|
|
note that `Σ_{n=1}^{b-1} ⌊na / b⌋ = Σ_{n=1}^{b-1} ⌊a(b - n) / b⌋`. Now apply
|
|
|
|
|
Exercises 4(a) and (b) to the bracket on the right.
|
|
|
|
|
-/
|
|
|
|
|
theorem exercise_7b : True := sorry
|
|
|
|
|
|
|
|
|
|
end Exercises.Apostol.Exercises_1_11
|